A value-added cooking process to improve the quality of soybean: Protecting its isoflavones and antioxidant activity - Lei Chen; Hui Teng; Jianbo Xiao (Food Science and Human Wellness)
This study investigated the effects of domestic cooking process on the variations of soybean isoflavones, aiming at understanding the conversion of β-glucosides and aglycones isoflavones during the process and the relation with antioxidant activity. It was found that β-glucosides isoflavones was significantly increased from 223.01 (raw) to 727.29 mg/g (frying at 160 °C for 2 min), but boiling showed only a slight increase to 258.14 mg/g. The process for the mixed cooking of soybeans with vegetables was also evaluated, which is quite common in home cuisine. The results showed all bioactive ingredients were aggressively destroyed by over processing, but interestingly, green pepper and kelp exhibited isoflavones generation potentials for soybean. In addition, cooking from 60 to 160 °C for 2 or 5 min, showed a significantly decrease on FRAP. However, in the case of fried soybeans which treated at 120 °C or 160 °C, when extending the heating time to 5 min, their FRAP activity got a significant increase. The present study may provide a practical guidance for healthy soybean cooking, by using frying around 120 °C for 5 min and mixed with some vegetables such as green peppers or kelp. Keywords: Soybeans, Isoflavones, Cooking processing, Antioxidant activity